Impaired Cognitive Flexibility and Working Memory Precedes Depression: A Rat Model to Study Depression - Margarita M. Maramis, Margarita
Abstract Introduction: Depressive disorders are the 4th leading cause of health problems and the 2nd leading cause of burden among all diseases. Almost all depressive disorder patients have cognitive impairments to a certain extend. Studies about cognitive impairments in depression had been conducted, but whether cognitive dysfunctions are the cause or the effect is still not clear.